Cultural Influences: Female Students’ Awareness and Perception Regarding Human Papillomavirus Vaccine - Nermen Abdelftah Mohamed PhD; Hassanat Ramadan Abdel-Aziz PhD; Mohamed Gamal Elsehrawy PhD (SAGE Open Nursing)
Background Human papillomavirus infection (HPV) is a highly prevalent sexually transmitted infection worldwide. HPV is responsible for about 70% of all worldwide cervical cancer incidence. Culture plays a critical role in shaping female perceptions and awareness of the HPV vaccine, influencing both individual and community-level health behaviors. There were only a few studies that had the subject in the place of study. The purpose of the study was to determine female students’ awareness and perception of the human papillomavirus vaccine. Methods A descriptive cross-sectional quantitative study was used. A convenient sampling technique was used following selection from the colleges of universities; 439 female students completed an online questionnaire. Structured interview questionnaire included three parts: demographic characteristics and medical history, awareness and knowledge questionnaire, and perception questionnaire. Results The studied female sample was 71.1% in the age range of 21 to 24 years old, 93.6% and 96.6% had not performed a Pap smear in the previous 3 years, and had not received the papillomavirus vaccine. And 58.8% of the total female study group had an accepted level of awareness regarding HPV and vaccines, 54.9% of the female study group had an accepted level of knowledge, and 36.4% of medical female students, as opposed to 18.5% of nonmedical students. Conclusion Female students lacked awareness, knowledge, and perception about the human papillomavirus.